Lorlatinib in advanced ROS1-positive non-small-cell lung cancer: a multicentre, open-label, single-arm, phase 1–2 trial. Issue 12 (December 2019) - Shaw, Alice T; Solomon, Benjamin J; Chiari, Rita; Riely, Gregory J; Besse, Benjamin; Soo, Ross A; Kao, Steven; Lin, Chia-Chi; Bauer, Todd M; Clancy, Jill S; Thurm, Holger; Martini, Jean-Francois; et al.
Summary: Background: Lorlatinib is a potent, brain-penetrant, third-generation tyrosine kinase inhibitor (TKI) that targets ALK and ROS1 with preclinical activity against most known resistance mutations in ALK and ROS1 . We investigated the antitumour activity and safety of lorlatinib in advanced, ROS1 -positive non-small-cell lung cancer (NSCLC). Methods: In this open-label, single-arm, phase 1–2 trial, we enrolled patients (aged ≥18 years) with histologically or cytologically confirmed advanced ROS1 -positive NSCLC, with or without CNS metastases, with an Eastern Cooperative Oncology Group performance status of 2 or less (≤1 for phase 1 only) from 28 hospitals in 12 countries worldwide. Lorlatinib 100 mg once daily (escalating doses of 10 mg once daily to 100 mg twice daily in phase 1 only) was given orally in continuous 21-day cycles until investigator-determined disease progression, unacceptable toxicity, withdrawal of consent, or death. The primary endpoint was overall and intracranial tumour response, assessed by independent central review. Activity endpoints were assessed in patients who received at least one dose of lorlatinib. This study is ongoing and is registered with ClinicalTrials.gov, NCT01970865 . Findings: Between Jan 22, 2014, and Oct 2, 2016, we assessed 364 patients, of whom 69 with ROS1 -positive NSCLC were enrolled. 21 (30%) of 69 patients were TKI-naive, 40 (58%) had previously received crizotinib as their only TKI, and eight (12%) had previously received one non-crizotinib ROS1 TKI or two or more ROS1 TKIs. The estimated median duration of follow-up for response was 21·1 months (IQR 15·2–30·3). 13 (62%; 95% CI 38–82) of 21 TKI-naive patients and 14 (35%; 21–52) of 40 patients previously treated with crizotinib as their only TKI had an objective response. Intracranial responses were achieved in seven (64%; 95% CI 31–89) of 11 TKI-naive patients and 12 (50%; 29–71) of 24 previous crizotinib-only patients. The most common grade 3–4 treatment-related adverse events were hypertriglyceridaemia (13 [19%] of 69 patients) and hypercholesterolaemia (ten [14%]). Serious treatment-related adverse events occurred in five (7%) of 69 patients. No treatment-related deaths were reported. Interpretation: Lorlatinib showed clinical activity in patients with advanced ROS1 -positive NSCLC, including those with CNS metastases and those previously treated with crizotinib. Because crizotinib-refractory patients have few treatment options, lorlatinib could represent an important next-line targeted agent. Funding: Pfizer.